Efektivitas Edukasi Gizi dengan Media Pembelajaran Interaktif Berbasis Android terhadap Peningkatan Pengetahuan tentang Makanan Jajanan Sehat Pada Siswa MIN 1 Jakarta - Patimah Indri Lestari (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2024)
Snack food is food and drink prepared and sold by street vendors on the streets and in other public crowded places which are eaten or consumed directly without further processing or preparation. Snack food has a negative impact if the food consumed does not contain sufficient nutritional value and is not guaranteed cleanliness and safety. One effort that can prevent health problems in students due to consumption of unhealthy snacks is to increase students knowledge about healthy snack food. The purpose of this study to determine the effectiveness of Interactive Learning Media (MPI) in increasing students knowledge about healthy snack food. It also aims to know differences in knowledge about healthy snack food before and after intervention with interactive learning media (MPI). This study uses a quantitative approach with an R&D method, employing a quasi-experimental pre-test post-test with a control group design. The population of this study consists of fifth-grade students. The sample comprises 84 students, with 42 students in the experimental group and 42 students in the control group. The data were analyzed using the Wilcoxon Signed Rank Test, Mann Whitney U-test, and N-Gain Score test. The statistical analysis of the Wilcoxon Signed Rank Test in the experimental group showed a p-value of 0.00, while in the control group, the p-value was > 0.142. The Mann Whitney U-Test analysis resulted in a p-value of 0.00. The N-Gain Score test produced a Gain score of 0.72. The study concluded that the product is effective in increasing knowledge about healthy street food.